Application of the project based learning model based on lesson study to improve Students' critical thinking skills - Rani Tania Pratiwi; Caecilia Dina Rosaline; Atin Nuryatin; Dewi Ningrum Agustin; Deden Agustira; Yulianti Yulianti; Tati Rahmawati; Muhammad Fahmi Fadli Rifa'i (PT Publikasiku Academic Solution, 2025)
This research aims to enhance critical thinking skills using the Lesson research-based project-based learning (PjBL) model in improving the critical thinking skills of grade VII students in social studies subjects at SMP Negeri 4 Ciawigebang. The theory supports this research. According to Trianto, which states that